A Study to Assess the Knowledge and Attitude of Family Members towards Ill-Effects of Alcoholism at Selected Hospital, Amritsar, Punjab (Global Journal of Medical Research, 2020)
Introduction: Alcoholism is one of the major health problems in the country and world over. It is the family problem and the most devastating impact occurs when the abuser is a parent. It affects the family members with the same intensity with which it affects the dependent person. The family as a unit would have to be assessed to delineate its strength and weakness in order to meet their well being. Therefore researcher feels the need to assess the level of knowledge and attitude of family members towards ill effects of alcoholism. The Objectives of the study were to assess the knowledge and attitude of family members towards ill effects of alcoholism, to find out association with selected demographic variables such as age, gender, educational status, habitat, monthly income, type of family, relationship with alcoholic and history of alcoholism in family on knowledge and attitude regarding ill effects of alcoholism and to find out relationship between knowledge and attitude score.
Keywords: knowledge; attitude; family members; ill-effects; alcoholism